2016
DOI: 10.1111/prd.12176
|View full text |Cite
|
Sign up to set email alerts
|

Initial and long‐term crestal bone responses to modern dental implants

Abstract: Successful osseointegration is the result of a controlled foreign body reaction to dental implants. Osseointegrated implants have demonstrated excellent long-term survivability, although they may be subject to limited marginal bone loss. Marginal bone loss during the first few years after implant placement seldom represents disease, but is instead the result of an adaptive bone response to surgical trauma and implant loading. It is not uncommon for implants with early marginal bone loss to enter a long-lasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
192
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(204 citation statements)
references
References 50 publications
5
192
0
7
Order By: Relevance
“…[21][22][23][24] Clinical evidence indicates that marginal bone loss around oral implants primarily depends on a complication to treatment due to unsuitable implant designs, poor clinical handling, and patients with different tissue complications 21,25,26 (Figure 2). However, periodontitis around teeth and marginal bone loss around oral implants have, in fact, little in common.…”
Section: Misunderstanding Of the Past; Marginal Bone Loss Solely Asmentioning
confidence: 99%
“…[21][22][23][24] Clinical evidence indicates that marginal bone loss around oral implants primarily depends on a complication to treatment due to unsuitable implant designs, poor clinical handling, and patients with different tissue complications 21,25,26 (Figure 2). However, periodontitis around teeth and marginal bone loss around oral implants have, in fact, little in common.…”
Section: Misunderstanding Of the Past; Marginal Bone Loss Solely Asmentioning
confidence: 99%
“…Some of these disagreements are related to the inconsistency in the case definition, case selection, and the variability in diagnostic thresholds for disease (Albrektsson, Chrcanovic, Ostman & Sennerby, 2017; Coli, Christiaens, Sennerby & Bruyn, 2017; Derks & Tomasi, 2015). Two recent systematic reviews indicated that homogeneity in peri‐implantitis reporting is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…15 This report is supported by finite element studies showing that excessive occlusal stress can concentrate at the implant marginal bone and cause microfracture within the bone. 19 Therefore, the baseline setting is considered to be important for evaluating marginal bone resorption, and to examine the influence of these various factors, it is required that unified standards that take the normal reaction of peri-implant bone into consideration. 18 Consequently, it is essential to understand how various factors influence bone resorption around implants.…”
mentioning
confidence: 99%